STUDY OF CONSUMER ACCEPTANCE ON TILAPIA (Oreochromis niloticus) SURIMI NUGGET - Nofrian, Rey; Buchari, Dewita; ', Desmelati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
The study of consumer acceptance on tilapia (Oreochromis niloticus) surimi nugget was conducted in Fisheries Product Technology Laboratory, and Fisheries Product Chemical Laboratory, Faculty of Fisheries and Marine University of Riau in April 2017. This study was aimed to determine the effect of tilapia fish surimi of consumer acceptance on tilapia surimi nugget. The methode used in this study was the experimental methode of tilapia surimi nugget processing. The design used was non-factorial Randomized Complete Design (RCD) with 4 treatment levels, namely N0: 500 g of Tilapia meat, N1: 500 g of Tilapia surimi, N2: 475 g of Tilapia surimi, N3: 450 g of Tilapia surimi, with 3 replicated, so the number of experimental units in the study was 12 units. Based on the level of consumer acceptance showed that the N1 treatment was most preferable for appearance, taste, aroma, and texture with value was 7.775, 7.825, 7.662, and 7.853, respectively. The characteristics of N1 treatment was a brownish yellow color of appearance, savory of taste, fish flavor more pronounced, aroma of fish, spices, solid and compact texture. While the best proximate result was N0 treatment with water content, protein content, fat content, ash content was 58.73%, 17.79%, 2.8861%, 2.295%, respectively.Keywords: Consumer Acceptence, Nugget, Oreochromis niloticus, Surimi